2003
DOI: 10.1144/gsl.sp.2003.218.01.20
|View full text |Cite
|
Sign up to set email alerts
|

Ophiolites as faithful records of the oxygen isotope ratio of ancient seawater: the Solund-Stavfjord Ophiolite Complex as a Late Ordovician example

Abstract: Fragments of the Ordovician sea floor preserved in the Solund-Stavfjord Ophiolite Complex in Western Norway serve as proxies for the δ18O of Ordovician seawater. The pillow basalt sections at Oldra and Strand are both enriched in 18O, recording their alteration by seawater at low temperature on the sea floor. In contrast, the sheeted dykes and gabbros generally are depleted of 18O, reflecting the modal proportion of secondary, low-18O chlorite and epidote formed from seawater at high temperature. These isotopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…Our knowledge of the oxygen isotope composition of oceanic crust (Table 5) comes from studies of ophiolites (Gregory and Taylor, 1981;Cocker et al, 1982;Agrinier et al, 1988;Lecuyer and Fourcade, 1991;Stakes and Taylor, 1992;Holmden and Muehlenbachs, 1993;Muehlenbachs et al, 2004), drill cores (Alt et al, 1986;Alt et al, 1995;Staudigel et al, 1995;Hart et al, 1999), xenoliths (Hansteen and Troll, 2003), and dredged material at fracture zones (Agrinier et al, 1995). Most of these are whole-rock or even composite studies, in order to achieve representative sampling of heterogeneous alteration.…”
Section: Oxygen Isotope Constraints On Oceanic Crust Recycling Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our knowledge of the oxygen isotope composition of oceanic crust (Table 5) comes from studies of ophiolites (Gregory and Taylor, 1981;Cocker et al, 1982;Agrinier et al, 1988;Lecuyer and Fourcade, 1991;Stakes and Taylor, 1992;Holmden and Muehlenbachs, 1993;Muehlenbachs et al, 2004), drill cores (Alt et al, 1986;Alt et al, 1995;Staudigel et al, 1995;Hart et al, 1999), xenoliths (Hansteen and Troll, 2003), and dredged material at fracture zones (Agrinier et al, 1995). Most of these are whole-rock or even composite studies, in order to achieve representative sampling of heterogeneous alteration.…”
Section: Oxygen Isotope Constraints On Oceanic Crust Recycling Modelsmentioning
confidence: 99%
“…This might explain the low d 18 O of Icelandic mantle sources, given the Pb isotopic evidence that they incorporate Lower Palaeozoic ocean crust (Thirlwall et al, 2004). However, there is no evidence whatsoever of unusually low d 18 O in the two Lower Palaeozoic ophiolites analyzed (Lecuyer and Fourcade, 1991;Muehlenbachs et al, 2004), and these are direct representatives of material that has most probably been recycled into the Icelandic mantle.…”
Section: Oxygen Isotope Constraints On Oceanic Crust Recycling Modelsmentioning
confidence: 99%
“…Instead, Kokfelt et al (2006) have suggested that d 18 O reflects ancient hydrothermal alteration and that low d 18 O would require unrealistic degrees of assimilation and fractionation (AFC) when local altered Icelandic crust would be considered, consistent with independent models (Stracke et al, 2003a). It is more plausible that large-scale hydrothermal alteration with meteoric fluids provided source rocks with low d 18 O (Gautason and Muehlenbachs, 1998) that were formed in, for example, Palaeozoic ophiolites (Muehlenbachs et al, 2004) and these were subsequently recycled.…”
Section: Significance Of the Li-he Isotope Correlation In Iceland Lavmentioning
confidence: 90%
“…Epidote forms at temperatures greater than ∼300°C, and is likely to precipitate from fully evolved vent fluids. Furthermore, epidosites and epidote-quartz veins in particular are thought to form preferentially along concentrated flow paths where water/rock ratios are high (29,(45)(46)(47) and are thus likely to be the best records of high-temperature fluids through time. Epidosites and epidotequartz veins from the two youngest oceanic crustal sections [Pito Deep and Site 504B (33,48)] have 87 Sr/ 86 Sr values that are close to typical average modern vent fluids, reinforcing the hypothesis that they record vent fluid chemistry in older rocks.…”
Section: Strontium Isotope Evolution In Hydrothermal Fluidsmentioning
confidence: 99%